Examining the Environmental Phillips Curve Hypothesis in the Ten Most Polluting Emerging Economies: Economic Dynamics and Sustainability - Sahin, Goktug; Naimoglu, Mustafa; Kavaz, Ismail; Sahin, Afsin (Mdpi, 2025)
In the context of the Environmental Phillips Curve hypothesis, this study investigates the impact of unemployment on environmental quality in ten emerging economies with the highest carbon emissions, as identified in the International Monetary Fund's 2015 World Economic Outlook. The primary aim of this study is to estimate the effects of income, natural gas usage, renewable energy usage, unemployment, and population size on carbon dioxide emissions in the selected countries. The study utilizes panel data from 1990 to 2019 and employs an Autoregressive Distributed Lag model (ARDL) to evaluate the short- and long-run relationships between these variables. Findings obtained using the Pooled Mean Group (PMG) estimator indicate that both income and population size have a significant positive impact on air pollution levels, whereas natural gas consumption and the use of renewable energy correlate with a decrease in emissions. The results support a negative correlation between unemployment and environmental degradation, aligning with the EPC. The error correction term suggests that the process returns to equilibrium in about 2.8 years. The findings are validated through robustness tests utilizing the Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) estimators. This study offers important insights for environmental policymaking in these emerging economies, emphasizing the importance of sustainable development strategies and green energy adoption.
Keywords: Environmental Phillips Curve; renewable energy; natural gas; unemployment; population; emerging economies